ANOTASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 49/PUU-X/2012 TENTANG UJI MATERIL PASAL 66 UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Septinierco Agraperta (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Abstract: Thesis entitled "Annotation Constitutional Court Decision No. 49 / PUU-X / 2012 on Judicial Review Article 66 of Law Number 30 Year 2004 concerning Notary”. Assessing the Constitutional Court Decision No. 49 / PUU-X / 2012 which stated that Article 66 paragraph (1) UUJN contrary to the Constitution of 1945. Article 66 paragraph (1) UUJN, set about investigating the authority with the approval of the Supervisory Council of Regions to call and check the relevant the notary deed that has been made. Problems formulated in this research is how the decision of the Constitutional Court Number 49 / PUU-X / 2012 against Article 66 UUJN testing, and how the legal implications of the Constitutional Court Decision No. 49 / PUU-X / 2012 on judicial review of Article 66 UUJN. This research is a normative law or legal research is normative juridical literature conducted by the search legal principles then made the interpretation of the public law rule which continued with the testing results and the interpretation of the theory or principles of public law. This study uses three methods of approach in the study of law, namely; Approach Legislation (Statute Approach), Approach Case (Case Approach), and History Approach (Historical Approach). The results showed that the Article 66 UUJN is not contrary to the principle of equality before the law. This decision also has implications for the investigator that the investigation process does not require further approval of the Supervisory Council of Regions to call Notary and / or take the minute of the deed stored related the deed he made which the implications for the Notary is when a Notary meets the demand Investigator to provide minutes of the deed or to provide information relating to the deed which made the Notary may violate the provisions of UUJN regarding the official oath and secrecy deed.  Additionally Notary may be liable for violating Article 322 of the code of civil law (KUHP). Keywords:    Judicial Review, Notary, Investigation